Microanalytical Studies Of The Distribution Of Organic Sulfur In Coal - R. Raymond (Society for Mining, Metallurgy & Exploration, 1986)
The occurrence and distribution of organic sulfur in coals may be investigated using electron probe microanalysis, scanning electron microscopy, and optical petrography. A general relationship exists between macerals and organic sulfur contents in individual coals: sporinite, resinite = micrinite, vitrinite > pseudovitrinite = semifusinite = macrinite > fusinite. With increasing organic sulfur content of a coal, the total range in organic sulfur content between macerals containing high and low organic sulfur contents likewise increases. Furthermore, the organic sulfur content of the vitrinite in most coals equals the organic sulfur content of the coal. For any individual coal, organic sulfur contents of macerals correlate inversely with reflectance-in-oil measurements, but the amount the organic sulfur contents vary between macerals cannot be calculated based solely on the coal's rank. Formation of pyrite following peatification has no effect on organic sulfur contents of surrounding macerals.